Gain Characteristics of Hybrid Waveguide Amplifiers in SiN Photonics Integration with Er-Yb:Al2O3 Thin Film - Ziming Dong; Guoqing Sun; Yuqing Zhao; Yaxin Wang; Lei Ding; Liqin Tang; Yigang Li (Photonics, 2025)
Integrated optical waveguide amplifiers, with their compact footprint, low power consumption, and scalability, are the basis for optical communications. The realization of high gain in such integrated devices is made more challenging by the tight optical constraints. In this work, we present efficient amplification in an erbium–ytterbium-based hybrid slot waveguide consisting of a silicon nitride waveguide and a thin-film active layer/electron-beam resist. The electron-beam resist as the upper cladding layer not only possesses the role of protecting the waveguide but also has tighter optical confinement in the vertical cross-section direction. On this basis, an accurate and comprehensive dynamic model of an erbium–ytterbium co-doped amplifier is realized by introducing quenched ions. A modal gain of above 20 dB is achieved at the signal wavelength of 1530 nm in a 1.4 cm long hybrid slot waveguide, with fractions of quenched ions fq = 30%. In addition, the proposed hybrid waveguide amplifiers exhibit higher modal gain than conventional air-clad amplifiers under the same conditions. Endowing silicon nitride photonic integrated circuits with efficient amplification enriches the integration of various active functionalities on silicon.